Effect of prucalopride on symptoms of chronic constipation. Issue 1 (20th September 2013) - Tack, J.; Stanghellini, V.; Dubois, D.; Joseph, A.; Vandeplassche, L.; Kerstens, R.
Abstract Background Prucalopride is a 5‐HT4 receptor agonist with gastrointestinal prokinetic activities. This integrated analysis of data from three 12‐week, double‐blind trials evaluated the effect of prucalopride 2 mg q.d. on common constipation symptoms in women in whom laxatives had failed to provide adequate relief. The effect of prucalopride on bowel function was outside the scope of the analysis and has been described elsewhere. Methods Women with self‐reported inadequate relief from laxatives and included in the prucalopride 2 mg or placebo arm of the trials were selected for analysis. Symptom severity was determined with the Patient Assessment of Constipation Symptoms (PAC–SYM) questionnaire. Observed changes from baseline in individual item scores were also evaluated by calculating Cohen's D effect sizes using baseline standard deviation (SD) (>0.2–0.5, >0.5–0.8 and >0.8 for small, moderate and large effects, respectively). Key Results Data were analyzed for 936 women. The proportion of women with a PAC‐SYM severity score >2 at baseline was 50.0% for abdominal symptoms, 71.4% for stool symptoms, and 15.5% for rectal symptoms. Excluding the women without presence of a symptom at baseline from the effect size calculations showed that prucalopride 2 mg had a large effect (>0.8) on all PAC‐SYM items, including abdominal pain, abdominal discomfort, bloating, straining, and painful bowel movements. For abdominal symptoms and stool symptoms, effect sizes with prucalopride 2 mg were 1.3–2.3 times larger than those with placebo. Conclusions & Inferences Prucalopride 2 mg q.d. for 12 weeks alleviates common constipation symptoms in women in whom laxatives had failed to provide adequate relief.